Human skin‐derived fibroblasts used as a 'Trojan horse' for drug delivery. (22nd February 2016) - Coccè, V.; Vitale, A.; Colombo, S.; Bonomi, A.; Sisto, F.; Ciusani, E.; Alessandri, G.; Parati, E.; Brambilla, P.; Brambilla, M.; La Porta, C. A.; Pessina, A.
Summary: Background: Drug toxicity currently represents the main challenge of tumour chemotherapy. Our group recently developed a new method for drug delivery inspired by the 'Trojan Horse' concept. Human mesenchymal stem cells (hMSCs) have been shown to play the role of new 'horses' in delivering anti‐tumour agents, without involving any genetic manipulation. As human stromal dermal fibroblasts (hSDFs) represent an interesting alternative to hMSCs, being easy to isolate, they could be an ideal candidate for this kind of procedure. Aim: To investigate whether hSDFs can take up and deliver paclitaxel (PTX) in sufficient concentrations to inhibit a very aggressive melanoma tumour (IgR39) in vitro . Methods: hSDFs were primed with high doses of PTX, and then the effect of drug delivery on IgR39 melanoma proliferation in vitro was evaluated using several assays (antiproliferation, transwell cocultures, rosette assays and colony growth assays). Furthermore, the cell cycle and PTX uptake/release mechanism of hSDFs were studied both under both normal and hypoxic conditions. Results: hSDFs incorporated PTX and then released it with unaffected pharmacological activity, inhibiting human IgR39 melanoma growth in vitro . The hypoxic conditions did not induce changes in cell cycle pattern and the uptake–release mechanism with PTX was not affected. Conclusions: hSDFs can be used as a Trojan horse, as the released drug was functionally active. These results indicated that these cells could be used for clinical treatment as the drug was released into the cellular environment and the primed cells underwent apoptosis.